Please, open this book! - Lehrhaupt, Adam (Simon & Schuster Books for Young Readers, 2015)
Books are made to be opened. Especially this one. But, guess what ... Someone closed this book! Who would do that? Luckily, you can fix this. All you need to do is open it. You can do that. Can't you? We need your help!